Unleashing talent in mental health sciences: gender equality at the top. (26th November 2018) - Breedvelt, Josefien J. F.; Rowe, Sarah; Bowden-Jones, Henrietta; Shridhar, Sunita; Lovett, Kate; Bockting, Claudi; Lingford-Hughes, Anne; Strathdee, Geraldine; Tracy, Derek K.
Summary: Society is undergoing a shift in gender politics. Science and medicine are part of this conversation, not least as women's representation and pay continue to drop as one progresses through more senior academic and clinical levels. Naming and redressing these inequalities needs to be a priority for us all. Declaration of interest: None.